Taxation Education in Secondary Schools - Morgan, Annette; Castelyn, Donovan (Australasian Tax Teachers Association, 2018)
This study evaluates what students in secondary schools are being taught about the Australian Taxation System and if those lesson are enough to benefit them when they became taxpayers. The study looked firstly at their experiences whilst at secondary school and the various course subjects that covered some form of education regarding the Australian Taxation System. Secondly the study asked the participations to consider if a more formal standardised approach to teaching taxation education in secondary school should be introduced and if they had received this themselves if it would have benefitted them when they first become taxpayers. The findings of the study found that the majority of the participations agreeing that a more formal structure should be introduced and that having a better understanding of taxation at the time entering into the taxation system would be of great benefit. It is suggested that the Education Department needs to work with the Australian Taxation Office and other relevant agencies to develop a standalone taxation education programme that is compulsory within all secondary schools in Australia rather than the ad hoc system that is currently being experienced by students.